Positive Interaction of Social Comparison and Personal Responsibility for Outcomes - Grygolec, Jaroslaw; Coricelli, Giorgio; Rustichini, Aldo (Frontiers in Psychology, 2012)
We formulate and test a model that allows a sharp separation between social versus private and personal responsibility versus chance in the evaluation of outcomes. In the experiment, subjects choose between two lotteries, one low-risk and one high-risk. They could then observe the outcomes. By varying the environment between private (in which they could only observe the outcome of the lottery they had not chosen) and social (they could observe the outcome of the lottery chosen by another subject) we can differentiate the response and brain activity following the feedback in social and private settings. The evidence suggests that envy and pride are significant motives driving decisions and outcomes evaluation, stronger than private emotions like regret and rejoice, with ventral striatum playing a key role. Focusing on outcomes evaluation stage we demonstrate that BOLD signal in ventral striatum is increasing in the difference between obtained and counterfactual payoffs. For a given difference in payoffs, striatal responses are more pronounced in social than in private environment. Moreover, a positive interaction (complementarity) between social comparison and personal responsibility is reflected in the pattern of activity in the ventral striatum. At decision stage we observe getting ahead of the Joneses effect in ventral striatum with subjective value of risk larger in social than in private environment.